The effects of conventional and unconventional monetary policy on exchange rate volatility - Wan Wei; Susan Pozo (Cogent Economics & Finance, 2021)
This paper examines the impacts of U.S. conventional and unconventional monetary policy announcements on the volatility of six exchange rates, namely Australian dollar, British pound, Canadian dollar, Euro, Japanese yen, and Swiss franc against the U.S. dollar. Narrow windows around policy announcements and high frequency second-by-second intraday data are used in the analysis. Results show that the exchange rate volatility increases significantly in the narrow window before and after the announcements under conventional monetary policy regime. The increase in the volatility is even greater during the contemporaneous period under the unconventional regime. Dividing monetary policy announcements into expansionary and non-expansionary groups, we further find that exchange rate volatility responds stronger to the non-expansionary announcements compared to the expansionary ones under the unconventional monetary policy regime.
Keywords: F31; G14; 330; Foreign exchange; High-frequency data; Monetary policy announcements; Unconventional Monetary Policy; Volatility